2023
DOI: 10.1093/gji/ggad029
|View full text |Cite
|
Sign up to set email alerts
|

Trans-dimensional Bayesian joint inversion of magnetotelluric and geomagnetic depth sounding responses to constrain mantle electrical discontinuities

Abstract: Summary Joint inversion of magnetotelluric (MT) and geomagnetic depth sounding (GDS) responses can constrain the crustal and mantle conductivity structures. Previous studies typically use either deterministic inversion algorithms that provide limited information on model uncertainties or using stochastic inversion algorithms with a predetermined number of layers that is generally not known a priori. Here, we present a new open-source Bayesian framework for the joint inversion of MT and GDS respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…We find that the contribution of proton for Earth‐relevant water contents is comparable to the sum of all other three conduction mechanisms in bridgmanite (i.e., the conductivity of dry bridgmanite) when hydrogen is incorporated as (Mg + 2H) Si or (Al + H) Si defects. The 1D conductivity‐depth profiles in the lower mantle, as determined from electromagnetic induction studies, are shown in Figure 8b (Chen et al, 2022; Civet et al., 2015; Civet & Tarits, 2013; Grayver et al., 2017; Kuvshinov & Olsen, 2006; Olsen, 1999a, 1999b; Puthe et al., 2015; Velimsky, 2010; Verhoeven et al., 2021; Yao, Ren, Pan, et al, 2023; Yao, Ren, Tang, et al, 2023). Most of these conductivity data fall within two orders of magnitude (0.1–10 S m −1 ) and generally remain nearly constant or slightly increase with increasing depth.…”
Section: Discussionmentioning
confidence: 99%
“…We find that the contribution of proton for Earth‐relevant water contents is comparable to the sum of all other three conduction mechanisms in bridgmanite (i.e., the conductivity of dry bridgmanite) when hydrogen is incorporated as (Mg + 2H) Si or (Al + H) Si defects. The 1D conductivity‐depth profiles in the lower mantle, as determined from electromagnetic induction studies, are shown in Figure 8b (Chen et al, 2022; Civet et al., 2015; Civet & Tarits, 2013; Grayver et al., 2017; Kuvshinov & Olsen, 2006; Olsen, 1999a, 1999b; Puthe et al., 2015; Velimsky, 2010; Verhoeven et al., 2021; Yao, Ren, Pan, et al, 2023; Yao, Ren, Tang, et al, 2023). Most of these conductivity data fall within two orders of magnitude (0.1–10 S m −1 ) and generally remain nearly constant or slightly increase with increasing depth.…”
Section: Discussionmentioning
confidence: 99%
“…The widely popular trans-dimensional Markov chain Monte Carlo (MCMC) method [24][25] realizes this inversion process. This method is widely used in the probabilistic inversion of geophysical electromagnetic data, including 1D layered models [26][27][28][29][30][31][32][33][34] and 2D Voronoi cells [35][36][37]. However, this method is computationally complex and expensive when extended to 3D Voronoi cells [38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity structure of the Earth's mantle provides important information about the geodynamic state of the Earth's mantle (Zhan et al, 2007;Karato, 2010;Weng et al, 2017;Chen et al, 2020Chen et al, , 2023Yao et al, 2023b). Geomagnetic data either from geomagnetic observatories or satellites typically covering a period range from several hours to several hundred days are sensitive to the conductivity structure of the Earth's mantle (Olsen, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the most recent work (Yao et al, 2023b), they developed a joint trans-D inversion based on an essentially single-chain sampling algorithm and physical parameter space for magnetotelluric data and local geomagnetic data from observatories. In their work, the model parameterization is treated as unknown and included in the inversion, determined by the data itself.…”
Section: Introductionmentioning
confidence: 99%